Analysis of Factors Affecting Student Learning Habits in the Age of Disruption - Rayuri, Intan; Indrawati, Henny; Caska, Caska (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Study habits are student learning behaviours that are formed from the process of learning and observing the surrounding environment both at home and at school. This study aims to analyse the factors that influence students' study habits in the Disruption Era. The population in the study of students majoring in social studies SMAN 14 Pekanbaru City. The sampling technique was random sampling. The sample size was 182 students. Data was collected by questionnaire. Data analysis technique Structural Equation Modeling (SEM) Partial Least Square (PLS). The results showed that the factors that influence students' study habits are factors of parental attention, interest in learning, and learning motivation. Therefore, children as students must get sufficient and directed attention from their parents. The existence of attention can lead to many positive emotional responses including the emergence of interest and motivation to learn in children as well as being able to form better study habits patterns in children in the Disruption Era. Rooted from that, it will also have an impact on the achievement of good learning outcomes in children at school.